Evaluation of maize (Zea mays) cultivars for their suitablity for babycorn under mid-hills of north-western Himalayas - THAKUR, D R; SHARMA, VINOD; PATHIK, S R (The Indian Journal of Agricultural Sciences, 2013)
Out of 30 cultivars of maize (Zea mays L.) evaluated for babycorn production at 2 locations (Bajaura and Sundernagar)during 1995-97, the hybrid 'VL 42' gave significantly highest marketable babycorn yield followed by hybrids 'MEH 133'and 'MEH 114'. All these hybrids remaining statistically at par with each other, had significantly higher cobs/plant thancomposite 'Early Composite Per cent husk and barrenness were less in hybrids than composite, whereas fodder yieldwas more in 'Early Composite' than hybrids. Removal of tassel just after its emergence gave 18% higher marketablebabycorn yield than no de-tasseling.